2020
DOI: 10.1101/2020.10.23.351775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA based SARS-CoV-2 vaccine candidate CVnCoV induces high levels of virus neutralizing antibodies and mediates protection in rodents

Abstract: The devastating SARS-CoV-2 pandemic demands rapid vaccine development and large scale production to meet worldwide needs. mRNA vaccines have emerged as one of the most promising technologies to address this unprecedented challenge. Here, we show preclinical data for our clinical candidate CVnCoV, a lipid nanoparticle (LNP) encapsulated non-modified mRNA vaccine that encodes the full length, pre-fusion stabilised SARS-CoV-2 Spike (S) protein. S translated from CVnCoV is cleaved, post-translationally modified, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 62 publications
3
35
1
Order By: Relevance
“…The degradation products were confirmed in vivo, as well as their secretion and the nontoxic nature of Lipid 319. This study of Lipid 319 is cited in the preclinical and clinical studies for SARS-CoV-2 as representing the Acuitas LNP class used in the BioNTech [ 49 ] and CureVac [ 53 , 69 ] products, although the Acuitas LNP delivering the self-amplifying RNA in the Imperial College London trial [ 60 ] is cited as having been contained in a more recent patent application [ 59 ], represented here by Lipid A9 from Acuitas ( Table 2 ). Recently, the identity of the Acuitas ionizable lipid in BioNTech’s approved BNT162b2 was disclosed [ 40 ] as ALC-0315 ( Table 2 ).…”
Section: Development Of Lipid Nanoparticles For the Current Sars-cmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation products were confirmed in vivo, as well as their secretion and the nontoxic nature of Lipid 319. This study of Lipid 319 is cited in the preclinical and clinical studies for SARS-CoV-2 as representing the Acuitas LNP class used in the BioNTech [ 49 ] and CureVac [ 53 , 69 ] products, although the Acuitas LNP delivering the self-amplifying RNA in the Imperial College London trial [ 60 ] is cited as having been contained in a more recent patent application [ 59 ], represented here by Lipid A9 from Acuitas ( Table 2 ). Recently, the identity of the Acuitas ionizable lipid in BioNTech’s approved BNT162b2 was disclosed [ 40 ] as ALC-0315 ( Table 2 ).…”
Section: Development Of Lipid Nanoparticles For the Current Sars-cmentioning
confidence: 99%
“…The CureVac mRNA LNP (CVnCoV) is a non-chemically modified, sequence-engineered mRNA encoding a diproline stabilized full-length S protein delivered in an Acuitas LNP, possibly using the ionizable lipid ALC-0315. The number of weeks between two doses was examined ranging, from 1 to 4 when using 2 µg doses in mice, where it was found that the longer intervals produced higher titers and T cell responses and a balanced Th1/Th2 response in Balb/c mice [ 53 ]. The second dose was required to produce neutralizing antibodies and two doses of 0.25 µg were insufficient to produce neutralizing antibodies.…”
Section: Mrna Lipid Nanoparticles In the Current Sars-cov-2 Clinicmentioning
confidence: 99%
“…Despite a high vaccine dose being utilized in our work [ 23 , 24 ], studies of the clinical candidates mRNA-1273 (Moderna), BNT162b2 (BioNTech/Pfizer) and CVnCoV (CureVac (Frankfurt, Germany)), all encoding a full-length, pre-fusion stabilized S protein ( Figure S1 ) [ 8 , 12 , 42 ] and ARCoV [ 43 ], encoding the RBD, reported that the production of SARS-CoV-2-specific Abs was driven by a significantly lower dose (ranging from 0.2 to 10 μg) of these vaccine candidates in mice. Importantly, various groups found that the Ab responses induced by these SARS-CoV-2 mRNA vaccines were able to neutralize the virus in vitro, as measured by both pseudovirus- and SARS-CoV-2-based neutralization assays [ 8 , 12 , 23 , 24 , 42 , 43 , 44 , 45 ], and that nAb levels were sustained for two months, or more, post-immunization [ 23 , 24 , 44 , 45 ]. Analyses of the Ab responses elicited by different vaccine doses indicated that mRNA vaccines induced a dose-dependent SARS-CoV-2-specific Ab response upon priming that was enhanced by a booster immunization [ 8 , 24 , 42 , 43 ].…”
Section: Immune Responses Elicited By Sars-cov-2 Mrna Vaccines: Lementioning
confidence: 99%
“…CureVac’s SARS-CoV-2 mRNA vaccine, although based on unmodified mRNA, is also encoding pre-fusion stabilized spike protein presented on the cell surface. This vaccine was also found to be highly immunogenic in mice and hamsters and induced strong neutralizing titers and full protection [ 74 ]. Two immunizations of 8 μg of this vaccine was required to induce well-detectable spike and RBD-binding antibodies as well as neutralization which resulted in protection from enhanced disease after challenge [ 75 ].…”
Section: Antibody Responses By Mrna Vaccines To Infectious Diseasementioning
confidence: 99%
“…The elicitation of T cell responses by mRNA vaccines against SARS-CoV-2 has been assessed in mice, in NHPs and in humans. The mRNA vaccines described above from CureVac, Moderna and BioNTech all elicited strong CD4+ and CD8+ T cells with Th1-type biased responses in mice [ 70 , 74 , 81 ]. Robust Th1-type CD4+ and CD8+ T cells in mice after administration of one or two doses of other LNP-formulated nucleoside-modified mRNA vaccines encoding the full-length spike protein or the RBD were also detected [ 82 , 83 ].…”
Section: T Cell Responses By Mrna Vaccinesmentioning
confidence: 99%